A tadpole grows up - Zollman, Pam. (New York : Children's Press, 2005)
- Format includes large color photographs, easy-to-read font, and simple interior design. - Series features vocabulary preview and review pages and backmatter, which gives young readers additional material to discuss or think about.
Word hunt -- Tadpoles! -- Frog and toads -- Laying eggs -- Tadpoles hatch -- Tadpoles change -- Tadpoles grow into frogs and toads -- Timeline: a tadpole grows up! -- Your new words -- These animals lay eggs in the water, too!
b
b
Keywords: Tadpoles -- Juvenile literature; Frogs -- Development -- Juvenile literature